Constrained discretion and central bank transparency - Francesco Bianchi; Leonardo Melosi (Federal Reserve Bank of Chicago, 2014)
We develop and estimate a general equilibrium model in which monetary policy can deviate from active in.ation stabilization and agents face uncertainty about the nature of these deviations. When observing a deviation, agents conduct Bayesian learning to infer its likely duration. Under constrained discretion, only short deviations occur: Agents are con.dent about a prompt return to the active regime, macroeconomic uncertainty is low, welfare is high. However, if a deviation persists, agents.beliefs start drifting, uncertainty accelerates, and welfare declines. If the duration of the deviations is announced, uncertainty follows a reverse path. For the U.S. transparency lowers uncertainty and increases welfare.
Keywords: E52; D83; C11; 330; Geldpolitik; Politische Kommunikation; Reputation; Regelbindung versus Diskretion; Inflationserwartung; Prospect Theory; Inflationsbekämpfung; Theorie; USA